Body mass index trends among adult U.S.Special Olympians, 2005-2010 - Foley, J. T.; Lloyd, M.; Temple, V. A. (Adapted Physical Activity Quarterly, 2013)
This study examined temporal trends in body mass index (BMI) among United States adults with intellectual disability (ID) participating in Special Olympics from 2005 to 2010. In addition, the prevalence of obesity was compared with published National Health and Nutrition Examination Survey (NHANES) statistics. After data cleaning, 6,004 height and weight records (male = 57 %) were available from the Special Olympics International Healthy Athletes Health Promotion database for the calculation of BMI. Rates of overweight and obesity were very high but generally stable over time. Compared with NHANES statistics, the prevalence of obesity was significantly higher for Special Olympics female participants in each data collection cycle. Integrated efforts to understand the social, environmental, behavioral, and biological determinants of obesity and among Special Olympics participants are needed.